NIVEL DE FINANCIAMIENTO Y RENTABILIDAD ECONÓMICA DE LAS ASOCIACIONES PRODUCTIVAS DE LA PARROQUIA YANGANA DEL CANTÓN LOJA. ESTUDIO DE CASO EN LA ASOCIACIÓN DE PRODUCTORES APÍCOLAS, AÑO 2014 - Ortíz Namicela, Patricia del Cisne (2015)
The research deals with how to implement appropriate measures to obtain a good level of financing and profitability in productive Associations Yangana parish Canton Loja, Case Study on the Association of beekeepers, 2014 strategies. The investigative process is empirical, as it involves applying new knowledge Field in documentary practice with a strategic prospective approach, the method is known as dialectical and techniques are: the survey interview, the documentary observation and bibliographic records. With the application of investigative techniques managed to fulfill the objectives, the first specific objective is: To characterize Productive Activities Associations Yangana parish, beginning with the identification of existing associations in the parish, through the technical research it was determined that three of beekeepers, growers and agribusiness; Unified partners constitute number thirty people, fifteen partners forming the Association of Beekeepers, the activity that meet these partnerships is to generate income, and its products sold in local markets without generating added value, in turn no funding external and not keep accounting records 6 enabling them to ascertain the real economic situation of the association and therefore making the right decisions. The second objective is to conduct an administrative, accounting and financial organization of beekeeping activity Yangana Parish; starting from a historical diagnosis and analysis of the current situation of the beekeeping association, organizational structure, beginning with the administrative part consists of the legal part, the accounting process and the respective financial ratios for future analysis and decision proposed decisions. The next objective is to identify funding sources to be applied in the beekeeping association Yangana parish; It was able to obtain information from financial institutions and decentralized autonomous governments, which contribute to strengthening the rural productive sector. The fourth objective mentions the analysis to the financial statements of the beekeeping association Yangana Parish; for compliance the respective vertical and horizontal analysis of financial statements that were built based on the information generated by the association for the years 2013 and 2014, and therefore the implementation of the respective 7 financial reasons that contributed to the analysis was applied financial, obtaining liquidity in the short and long term efficiency that the association uses its assets through asset turnover and hence profitability allowing you to continue with the proposed activities, their estimates for making best decisions for the Asociation. Finally representatives of the beekeeping association is recommended administrative organization and accounting process for financial analysis annually its financial reports in order to determine the economic reality and timely decision based on the results is made.